Islamic banking as a mechanism for financing start-ups - Abdellatif, Haddadi; Embarka, Lensari; Lalafatma, Reggani (International journal of economic perspectives, 2024)
This research paper aims to highlight some Islamic financing formulas in Islamic banks that may provide the necessary financing and support to Start-ups in accordance with their formation and needs, especially in light of the lack of necessary experience and lack of sufficient guarantees. It has been concluded that Islamic banks may provide the necessary support and financing that It is needed by Start-ups through a set of formulas such as Musharaka, Murabaha and Ijarah.